Effect of N-(6-aminobenzo[d]thiazol-2-yl)benzamide and 2,6-diamino-benzothiazole as Corrosion Inhibitor in acid medium (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
2-amino-6-nitrobenzothiazole(ANBT) was used as an inhibitor for the corrosion of mild steel in acid medium since the inhibition efficiency was low for that compound, 2,6-diaminobenzothiazole (DABT) and N-(6-aminobenzo [d] thiazol-2-y1) benzamide(ABTB) was synthesized, Â and characterized by FT-IR, H1NMR, and C13NMR.The synthesized compound was tested as a corrosion inhibitor for mild steel in 1N HCl solution using weight loss, Potentiodynamic polarization, and AC impedance techniques. The inhibition efficiency was studied at the different time, temperature and acid concentration by weight loss method. The values of activation energy and free energy of adsorption of these compounds were also calculated, which reveals that the inhibitor was adsorbed on the mild steel by physisorption mechanism. Adsorption obeys Langmuir and Temkin adsorption isotherms. The results obtained by weight loss method revealed that the compound performed as a better inhibitor for mild steel in 1N HCl. Potentiodynamic polarization studies showed that the inhibitor acts as a mixed type inhibitor.AC impedance studies revealed that the corrosion process was controlled by charge transfer process. Surface analysis was studied using SEM and FT-IR.